Power flow management of triple active bridge for fuel cell applications - Nageswara Rao Kudithi; Sakda Somkun (Institute of Advanced Engineering and Science, 2019)
The power conditioning circuits which are used in fuel cell systems should carefully be designed to prolong the life span of the system, for the reason of the dynamic nature, such that the unexpected and extreme changes in load decreases the life of the fuel cells. This paper presents the triple active bridge (TAB) and it’s average small signal modelling, which is used for design of the system controllers for stable operation. The extended symmetrical optimum method is used for realized the proportional integral (PI) controller, to control the output/Load voltage and power flow in the fuel cell/Source with a guaranteed minimum phase margin for the system with a variable process gain in addition to other accepted desired performances. This method ensures the maximum phase margin at a minimum required value at the desired gain crossover frequency with a compromise between system’s peak overshoot, rise time and settling time. This model and this approach helps in designing TAB suitable for healthy and uninterrupted fuel cell power generation systems as a part of a renewable /clean energy system. MATLAB/Simulink is used to simulate the proposed controllers with TAB.